The novel metabotropic glutamate receptor 2 positive allosteric modulator, AZD8529, decreases nicotine self-administration and relapse in squirrel monkeys - Justinova, Zuzana (Biol Psychiatry, 2015)
BACKGROUND: Based on rodent studies, Group II metabotropic glutamate receptors (mGluR2 & 3) were suggested as targets for addiction treatment. However, LY379268 and other Group II agonists do not discriminate between the mainly presynaptic inhibitory mGluR2 (the proposed treatment target) and mGluR3. These agonists also produce tolerance over repeated administration and are no longer considered for addiction treatment. Here, we determined the effects of AZD8529, a selective positive allosteric modulator (PAM) of mGluR2, on abuse-related effects of nicotine in squirrel monkeys and rats. METHODS: We first assessed modulation of mGluR2 function by AZD8529 using functional in-vitro assays in both membranes prepared from a cell line expressing human mGluR2 and in primate brain slices. We then determined AZD8529 (0.03-10 mg/kg, i.m.) effects on intravenous nicotine self-administration and reinstatement of nicotine seeking induced by nicotine priming or nicotine-associated cues. We also determined AZD8529 effects on food self-administration in monkeys and nicotine-induced dopamine release in accumbens shell in rats. RESULTS: AZD8529 potentiated agonist-induced activation of mGluR2 in both the membrane-binding assay and in primate cortex, hippocampus, and striatum. In monkeys, AZD8529 decreased nicotine self-administration at doses (0.3-3 mg/kg) that did not affect food self-administration. AZD8529 also reduced nicotine priming- and cue-induced reinstatement of nicotine seeking after extinction of the drug-reinforced responding. In rats, AZD8529 decreased nicotine-induced accumbens dopamine release. CONCLUSIONS: Our results provide evidence for efficacy of PAMs of mGluR2 in non-human primate models of nicotine reinforcement and relapse. We propose that this drug class should be considered for nicotine addiction treatment.